2022
DOI: 10.1016/j.jpsychires.2022.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Maternal fear of COVID-19 and prevalence of postnatal depression symptoms, risk and protective factors

Abstract: This is a multicenter prospective observational study, aimed to evaluate the relations between Fear of COVID-19 and postpartum depression (PPD) symptom, that included a cohort of women who delivered during COVID-19 lockdown between 03 and 05/2020. Participants were approached after delivery and asked to complete an online questionnaire. Data was verified with each center's perinatal database. The validated Fear of COVID-19 Scale was in use. PPD was evaluated using the EPDS questionnaire as a categorical (≥13) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition, the present findings demonstrate a slight (but not significant) increase in distress from pregnancy to 6-weeks postpartum. Similarly, prior longitudinal research conducted during the pandemic reported elevated levels of depression from pregnancy to the first few months of postpartum (Duguay et al, 2022;Gluska et al, 2022). Research prior to the pandemic identified 12 weeks postpartum as the period with the highest prevalence of postpartum depression, with a marked decline thereafter (Liu et al, 2021).…”
Section: Distress Levels Across Time: Pregnancy To 15-months Postpartummentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, the present findings demonstrate a slight (but not significant) increase in distress from pregnancy to 6-weeks postpartum. Similarly, prior longitudinal research conducted during the pandemic reported elevated levels of depression from pregnancy to the first few months of postpartum (Duguay et al, 2022;Gluska et al, 2022). Research prior to the pandemic identified 12 weeks postpartum as the period with the highest prevalence of postpartum depression, with a marked decline thereafter (Liu et al, 2021).…”
Section: Distress Levels Across Time: Pregnancy To 15-months Postpartummentioning
confidence: 84%
“…In addition, other studies have followed participants from pregnancy to the postpartum, during the pandemic, and have shown elevated rates of mental health problems. For example, Gluska et al (2022) showed that women in Israel experienced increased levels of depressive symptoms from 3-to 6-months postpartum during the pandemic. Additionally, a study of pregnant people in Quebec, Canada, found that prenatal maternal distress was associated with distress at 2-months postpartum, and that postpartum distress mediated the association between prenatal distress and early infant social-emotional development (Duguay et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…During T1, 1079 (74%) were contacted by phone. In total, 774 (53%) consented to answering the online questionnaires, and 429 (29%) answered over 70% of the questionnaires [ 19 ] and were later re-approached at T2. Among them, 377 (87.9%) gave their consent, and 246 completed at least 70% of the T2 questionnaires and thus entered the analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, social distancing and lockdowns have led to limited maternal social support networks, as well as limited access to health care services. This, in turn, has increased the maternal risk for the development of psychological disorders [ 15 , 19 ]. Moreover, the use of personal protective equipment was found to be an independent factor for developing depressive and post-traumatic stress symptoms during the postpartum period [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For mothers, thinking about the consequences of COVID-19 was strongly associated with fear, anxiety, 9 and maternal depression. 10 Pandemic-related fears have been associated with increased mental health problems, especially among those with a history of depression. 11 However, it is hypothesized that mothers’ fears for their children could also impact their own mental health, especially depression and anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%